Pest management and food production: looking to the future - Yudelman, Montague; Ratta, Annu; Nygaard, David F. (International Food Policy Research Institute, 1998)
In their comprehensive paper, Montague Yudelman, Annu Ratta, and David Nygaard examine the key issues with regard to pest management and food production over the coming decades. They draw attention to the lack of adequate information on the magnitude and impact of pest losses; with out such information, policy makers are handicapped when devising strategies for meeting food needs. The authors address both chemical and nonchemical approaches to pest management, high lighting the importance of biotechnology. There is growing public sentiment against biotechnology but little appreciation as yet of its contributions to alleviating hunger by, among other things, controlling pest losses. The authors also adress the important subject of the roles of different actors in pest management, most notably the private sector. A world with out pests is unrealistic and probably undesirable. However, a world with severely reduced losses of food production to pests is achievable by 2020. This paper shows us how.